The effect of age on outcomes at a cardiac rehabilitation center in Turkey - Pınar Demir Gündoğmuş; Berrin Topçu Özcan; Mert Hayıroğlu; İbrahim Gündoğmuş; Emrah Burak Ölçü; Mehmet Uzun; Ahmet L. Orhan (KARE Publishing, 2020)
Objective: The aim of this study was to assess the effectiveness of a 12-week phase II cardiac rehabilitation (CR) program in Turkish patients aged between ≤65 years and >65 years using psychical parameters, echocardiography measurements, lipid profiles, and psychological parameters. Methods: A total of 68 patients who completed a phase II CR program were enrolled in this retrospective study. The echocardiography measurements, as well as assessment of physical parameters, psychological state, and serum lipid level of the patients were evaluated before the entry into the program and just after the completion. Patients were divided into 2 groups: those aged 65 years and under and those over the age of 65, and the effects of the CR program were compared. Results: There was a statistically significant difference in the average heart rate (HR), left ventricular ejection fraction (LVEF), Beck Depression Inventory (BDI) score, and State-Trait Anxiety Inventory (STAI) I-II scores of young patients before and after cardiac rehabilitation. The LVEF, high-density lipoprotein (HDL), BDI, STAI-I, and STAI-II parameters of older patients were statistically significant. In the comparison between those who were 65 years and under and those over the age of 65, the change in the mean HR (+11.24+-12.62 bpm vs. +3.96+-12.50 bpm; p=0.039), LVEF (+21.31+-21.37% vs. +9.55+-13.50%; p=0.035) and STAI I scores (-11.33+-11.51 points vs. -23.25+-14.08 points; p=0.025) were significantly different. Conclusion: The results of the present study revealed that patients in a Turkish population aged 65 and over benefited from CR as much as younger patients did in terms of physical parameters, echocardiography measurements, lipid profiles, and psychological parameters.